1992
DOI: 10.1128/iai.60.1.111-116.1992
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between capsular type and virulence for mice among human isolates of Streptococcus pneumoniae

Abstract: The relationship between capsular type and virulence for mice was examined with 69 fresh human isolates of Streptococcus pneumoniae. These isolates represented eight capsular types or groups. Serologic and molecular weight differences in PspA (pneumococcal surface protein A) indicated that the strains were clonally distinct. Mice were infected intravenously with washed bacteria of all 69 isolates in sterile salt solutions. Twenty-eight of the isolates were also injected intraperitoneally to permit comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(96 citation statements)
references
References 28 publications
1
89
0
6
Order By: Relevance
“…Pneumococci are divided into serotypes based on the capsular polysaccharides they produce. Since different pneumococcal serotypes have varying tendencies toward nasopharyngeal colonization or invasiveness [10,11], the hypothesis was formed that urinary antigen detection would vary by serotype. Previous studies have suggested that capsular polysaccharide serotypes with less metabolic cost (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumococci are divided into serotypes based on the capsular polysaccharides they produce. Since different pneumococcal serotypes have varying tendencies toward nasopharyngeal colonization or invasiveness [10,11], the hypothesis was formed that urinary antigen detection would vary by serotype. Previous studies have suggested that capsular polysaccharide serotypes with less metabolic cost (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococci are divided into serotypes based on their capsular polysaccharide structure, which is considered to be the most important virulence factor [9], and there are serotype-specific differences in nasopharyngeal carriage prevalence and disease incidence [10,11]. These observations gave rise to the hypothesis that the utility of UAT would vary depending on the pneumococcal serotypes, and that there would be a change in the positive rate of UAT in accordance with changes in the distribution of pneumococcal serotypes that may have occurred since the introduction of the 13-valent pneumococcal conjugated vaccine (PCV13).…”
Section: Introductionmentioning
confidence: 99%
“…A list of all bacterial strains, plasmids, and primers is provided in Table 1. Streptococcus pneumoniae EF3030 is a serotype 19F strain which typically establishes nasopharyngeal carriage or localized airway infection in murine models (Briles et al, 1992;Palaniappan et al, 2005). Pneumococci were grown on trypticase soy agar (BD) supplemented with 5% defibrinated sheep blood (Hemostat) and 4 lg mL À1 gentamicin.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Clinical isolates of S. pneumoniae wild-type (WT) strains D39, 6B, 19F, 23F and NTHi WT strain 12 were used in this study (Avery et al, 1979;Briles et al, 1992;Shuto et al, 2001;Jono et al, 2002). Unless specified, S. pneumoniae WT strain D39 was commonly used to treat human epithelial HeLa cells in this study.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%